Organic waste supplementations as alternative substrate for cultivation of the grey oyster mushroom Pleurotus pulmonarius (FR.) QUELET / Tang Chen Seok - Tang , Chen Seok (2019)
Mushroom industry plays an important role in health and nutrition as well as economic resources in both urban and rural areas. Due to the limitation of raw materials supply and the increasing cost of substrate especially sawdust for mushroom cultivation, coffee waste (CW), food waste compost (FWC) and empty fruit bunch compost (EFBC) were selected as alternative supplemented substrates to cultivate grey oyster mushroom, Pleurotus pulmonarius. The objectives of this study were to optimise the substrate formulations and to evaluate the growth performance, production yield of P. pulmonarius grown on the standard substrate supplemented with varying concentrations of CW, FWC and EFBC along with analysing the nutrient profile of selected P. pulmonarius fruiting bodies. In this study, P. pulmonarius strains (S01 and S02) were grown and the linear growth study for P. pulmonarius strains (S01 and S02) grown on standard substrate supplemented with different concentrations (10 %, 20 %, 30 % and 40 % (w/w)) of CW, FWC and EFBC were carried out. The strains tested showed variable growth rates and mycelium compactness on each supplemented wastes at different concentrations. Based on the linear growth study, a total of eight substrate formulations for both strains initially chosen for the bag preparations, included: control substrate and 10 % (w/w) of CW supplementation for both strains respectively, 10 % (w/w) of FWC supplementation for strain S01, 20 % (w/w) of FWC supplementation for strain S02 and 30 % (w/w) of EFBC supplementation for both strains. It was observed that the supplementation of various wastes at their lower concentrations had enhanced mycelium growth and only fast growth rate with dense mycelium may reflect the utilisation of nutrient resources is optimum. In order to select a comparatively more suitable strain to be used in nutrient analysis for P. pulmonarius, an evaluation and comparison of growth performance, yield and biological efficiency (BE) among the strain was conducted. Strain S02 has proved to have fast colonisation, short pinheads development, strong pathogenicity, higher percentages of successfully fruiting bags, better yield and BE than strain S01. Thus, strain S02 were selected and analysed for nutritional attributes. There were high protein content in P. pulmonarius compared to sugar, phenolic and β-glucan. The protein content was significantly higher (p < 0.05) in all substrate supplemented with wastes compared to the control substrate. Hence, the efficiency of mycelium in transforming the chemical compositions of substrate and different wastes into fruiting bodies itself can cause the variations among the nutritional attributes of P. pulmonarius. Strain S02 grown on standard substrate supplemented with 20 % (w/w) of FWC recorded the highest biological efficiency (101.40±29.92 %) and the fruiting bodies contained the highest β-glucan content (29.58 ± 0.01 %). The days required for mycelium running was 24.87±3.10 and the pinheads formation was 14.13±3.10. In conclusion, CW, FWC and EFBC can be utilized as supplement in the cultivation of grey oyster mushrooms and an alternative way for solid waste management.